Emergency cesarean section in a pregnant woman with Freeman-Sheldon syndrome and acute respiratory distress. A Case report - Viviana de la Caridad Sáez Cantero (Medisur)
Freeman-Sheldon syndrome is a rare genetic disorder characterized by a wide spectrum of bone abnormalities, joint contractures, and typical facial features. Facial abnormalities of microstomia, micrognathia, and macroglossia constitute an impediment to accessing the airway. On the other hand, skeletal alterations such as joint contractures and scoliosis are a restrictive component for both respiratory function and the evolution of pregnancy. The case of a pregnant woman with Freeman-Sheldon syndrome and a genetic diagnosis of a fetus with stigmata of the syndrome is presented. This patient required termination of pregnancy by emergency cesarean section due to acute respiratory distress secondary to chronic polyhydramnios. Planning the course of action to follow, whether anticipated or emergency, accompanied by a multidisciplinary team, is decisive in the proper management of patients with these characteristics.